CaWO4 crystals as scintillators for cryogenic dark matter search; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 537, iss. 1-2 - Ninkovic J.; Angloher G.; Bucci C.; Cozzini C.; Frank T.; Hauff D.; Kraus H.; Majorovits B.; Mikhailik V.; Petricca F.; Probst F.; Ramachers Y.; et al. (2005, 2005)
Title screen